KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SD MELALUI MODEL PROBLEM BASED LEARNING BERBANTU QUIZIZZ - Hasti Arum Nastiti; Honest Ummi Kaltsum (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Problem solving skills are important for students and must receive special attention so that all students can understand and master the ability to solve a problem in the teaching and learning process of mathematics. The importance of this makes learning mathematics require a model that is able to hone students' abilities in solving mathematical problems. This study aims to describe the mathematical problem solving ability of sixth graders through the application of the Quizizz-assisted Problem Based Learning model. This type of research uses descriptive qualitative research with a phenomenological research design. Data collection techniques used observation, interviews and documentation. The data analysis technique used qualitative data analysis with three steps, namely data reduction, data presentation, and data verification. The result of this research is that by learning through the Problem Based Learning model assisted by Quizizz students are able to solve mathematical problems better. The conclusion of this study is that the application of the Problem Based Learning Quizizz model is effective in students' mathematical problem solving abilities. Students feel that learning the Problem Based Learning model is easier, plus the use of Quizizz makes students feel happy and challenged to solve math problems.